Exploring the Role of Ownership in International Entrepreneurship: How does Ownership Affect Internationalisation of Polish Firms? - Krzysztof Wach (Entrepreneurial Business and Economics Review, 2017)
Objective: The article focuses on the role of ownership in the process of entrepreneurial internationalisation of the firm. The main objective of the article is to verify whether and how ownership impacts on the level of internationalisation.